2011
DOI: 10.3998/ark.5550190.0012.b14
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient one-pot three-component Mannich reaction catalyzed by ZnO-nanoparticles in water

Abstract: ZnO-nanoparticles, as a recyclable heterogeneous catalyst, efficiently promoted the one-pot threecomponent Mannich reaction of ketones, aromatic aldehydes and amines in water to afford the corresponding β-amino carbonyl compounds in good to excellent yields and with moderate diastereoselectivity. The method offers a new modification of the Mannich reaction with a simple workup procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In 2011, MaGee et al reported a rapid and efficient method for the one-pot Mannich reaction of aldehydes, ketones and amines in the presence of ZnO-nanoparticles. 49 Under the optimized procedure, the reaction was carried out with 4-chlorobenzaldehyde, aniline and cyclohexanone using 0.5 mmol ZnO nanoparticles as the catalyst in water at 60 °C to afford the products in high yields ( Scheme 18 ). This procedure was applied to a wide variety of aromatic aldehydes and amines bearing electron-withdrawing and electron-donating groups to offer facile access to β-amino ketones in excellent yields (74–93%) and with anti-selectivity.…”
Section: Zn-catalysed Mannich Reactionsmentioning
confidence: 99%
“…In 2011, MaGee et al reported a rapid and efficient method for the one-pot Mannich reaction of aldehydes, ketones and amines in the presence of ZnO-nanoparticles. 49 Under the optimized procedure, the reaction was carried out with 4-chlorobenzaldehyde, aniline and cyclohexanone using 0.5 mmol ZnO nanoparticles as the catalyst in water at 60 °C to afford the products in high yields ( Scheme 18 ). This procedure was applied to a wide variety of aromatic aldehydes and amines bearing electron-withdrawing and electron-donating groups to offer facile access to β-amino ketones in excellent yields (74–93%) and with anti-selectivity.…”
Section: Zn-catalysed Mannich Reactionsmentioning
confidence: 99%
“…This reaction produces β-amino carbonyl compounds from three components: an amine, an aldehyde, and an enolizable ketone. β-amino carbonyl compounds, also known as a Mannich bases, are important intermediates for the synthesis of many pharmaceutical and natural products containing nitrogen in their structures (51)(52)(53)(54).…”
Section: Synthetic Derivatives Of Lawsonementioning
confidence: 99%
“…In 2011, Dabiri et al (56) reported the synthesis of lawsone Mannich bases (HL14-33) via reflux heating over 5-7 hours, using water-like solvent and a InCl 3 (indium trichloride) -like catalyst; the results showed yields of 78% to 90%, thus, an easy, efficient and clean method for their production was defined (Table 1). Using the Mannich reaction with lawsone, various amines and substituted benzaldehydes is a good alternative to synthesizing amino derivatives of 2-hydroxy-1,4-naphthoquinone, since these methods have proved to be efficient, environmentally clean and simple, with high atomic economy (51)(52)(53)(54)(55)(56)(57)(58). Furthermore, the synthesized compounds have demonstrated antibacterial (55), antiparasitic (47) and molluscicidal activity (59).…”
Section: Synthetic Derivatives Of Lawsonementioning
confidence: 99%